Biometric Indices and Condition factors of Pomadasys jubelini (Cuvier, 1830) from Obuama Creek, Nigeria - Olaniyi Alaba Olopade; Henry Eyina Dienye; Cynthia Chigazu Okonkwo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Biometric indices of Pomadasys jubelini from Obuama Creek, Rivers state, Nigeria were investigated using length frequency distributions (LFDs), length-weight relationships (LWRs), length-length relationships (LLRs), condition factors (allometric, KA, Fulton’s, KF and relative, KR). Specimens were captured in a stretch of the creek from March to September 2019. A total of 229 specimens were examined with the total length (TL) and weight (W) ranging from 8.7 to 50.4 cm and 8.7 to 834.5 g respectively. The standard length (SL) ranged from 5.3 to 46.8 cm, fork length (FL) was between 6.5 to 48.7 cm and the girth length (GL) varied from 4.7 to 38.7 cm. The relationships of weight-length showed a negative allometric growth pattern with a value of "b" of 2,666. Fulton's condition factor (KF) ranged from 0.10 to 5.45, with an average of 1.21±0.66 indicating perfect wellbeing for the species. The LLR's allometric coefficient ' b ' between TL vs. FL and TL vs. GL showed positive allometric growth, while SL vs. FL, SL vs. TL, SL vs. GL, and GL vs. TL showed negative allometric growth, although the values were close to 1. These findings also provided some new and updated information on some of the morphometric characters of Pomadasys jubelini in Obuama Creek that could be useful for fisheries management and fish species protection measures in the creek and adjacent habitats.